Esters of 6-aminohexanoic acid as skin permeation enhancers : The effect of branching in the alkanol moiety - Hrabálek, Alexandr; Vávrová, Kateřina; Doležal, Pavel; Macháček, Miloš (Journal of pharmaceutical sciences, 2005)
In order to investigate the effect of branching and cyclization in the hydrophobic part of skin permeation enhancers, 17 novel branched-chain and cyclic 6-aminohexanoic acid esters were prepared. Their permeation enhancing activity was evaluated in vitro using human skin and theophylline as a model drug, and compared to that of the corresponding linear-chain analogues. The results showed that chain branching and cyclization has a negative influence on the enhancing activity of 6-aminohexanoates. For example, the enhancement ratios (ERs) of dodecan-1-yl, dodecan-2-yl, dodecan-4-yl, and cyclododecyl ester were 39.7, 29.3, 3.1, and 2.2, respectively. No significant change in the optimum length of the chain was observed. Dodecan-2-yl 6-aminohexanoate, the most active branched derivative, still maintains a remarkable enhancing activity (ER 29.3). Presumably, the relatively small degree of branching of these molecules does not prevent them from interacting with the lipid components of the stratum corneum. However, a higher degree of branching, cyclization of the chain, and presence of an aromatic ring resulted in a loss of activity. (c) 2005 Wiley-Liss, Inc.
Keywords: Chromatography, High Pressure Liquid; Alcohols; techniky in vitro; Humans; kožní absorpce; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; financování vládou; Female; Aminocaproates; lidé; magnetická rezonanční spektroskopie; kyselina 6-aminokapronová; Esters; ženské pohlaví; Male; Financing, Government; Skin Absorption; In Vitro Techniques; aminokapronáty; Aminocaproic Acid; Magnetic Resonance Spectroscopy; mužské pohlaví; vysokoúčinná kapalinová chromatografie; alkoholy; estery